Transferts méthodologiques 3D appliqués à l’étude de l’art paléolithique : une nouvelle dimension pour les relevés d’art préhistorique - Oscar Fuentes; Julie Lepelé; Geneviève Pinçon (In Situ)
All studies concerning Palaeolithic art (parietal or movable art) are based on analytical recordings of the kind now practiced for over a century. This analytical approach is indispensable for our understanding of the thought processes of prehistoric societies. But today, new 3D technologies are having a massive impact on research practices, as was the case with photography. An initiative by the Centre national de Préhistoire led to the development by an archaeologist specialising in parietal art, working in collaboration with a 3D-graphics designer, of a new way of applying 3D techniques to rock art. This makes it possible to go beyond the limits inherent in traditional approaches (2D recordings): graphic expressions can at last be studied in their three-dimensional context. We have chosen to use 3D resources in order to set up a dialogue between two operational frameworks (2D and 3D) which we propose to illustrate in this article, using the example of the decorated cave of Comarque (Dordogne). We base our approach on the use of Blender software (Open Source) which offers a panoply of tools useful for the analysis of parietal works. In particular, it is possible to project vectorial recordings made in 2D onto a 3D model. But above all it is possible to produce a record directly on the 3D model while keeping all the information relating to volume. This introduction of new 3D technologies for rock art recording may also encourage archaeologists to re-examine the methodological questions on which they base their analyses.